The fingerprint and its role in enriching the expression on the surface of the plastic painting - Alsedairy, Maha Mohammed (Journal of Educational and Psychological Sciences, 2022)
The research aimed to take advantage of the superficial impact of tools and materials in the production of compositional panels, in addition to detecting the impact of the fingerprint and employing its technology on the surface of the painting to enrich the field of plastic painting, this research followed the analytical descriptive approach in reviewing the theoretical framework and an analytical reading of some of the works of Saudi artists who dealt with the technique of impacting the material on the surface of the painting, By selecting a collection of paintings based on the use of a range of materials with a special texture and employing the effect of their texture on different surfaces to show aesthetic dimensions. Several results have been reached, including: access to aesthetic values through the use of various materials to employ their texture on the plastic panel flat. Fingerprint technology increases the artist’s perception and awareness by trying and experimenting in creating linear relationships and their interconnection between parts of the artwork. Each artist has his own distinctive style and performance methods for the fingerprint vary from artist to artist in the method of plastic processing and the method of distributing fingerprints on the flat of the painting, which has earned the work expressive values that distinguish each artist by the nature of his work. The researcher recommended the work of studies and researches containing the documentation of fingerprint technology experiments for Saudi artists to preserve the history of technical development in Saudi Arabia, and to increase interest in the concept of fingerprint and its types as a formative value in the field of plastic painting.